Sibling-Controlled Study of Parental Bonding, Coping, and Urgent Health-Care Use in Families With Children With Nonepileptic Seizures. (9th July 2018) - Bursch, Brenda; Forgey, Marcy; Emerson, Natacha D; Siddarth, Prabha; Weisbrot, Deborah M; Shaw, Richard J; Doss, Julia; Falcone, Tatiana; Hinman, Kyle; LaFrance, W Curt; Laptook, Rebecca; Willis, Matthew D; et al.
Abstract: Objectives: Pediatric psychogenic nonepileptic seizures (PNES) is a functional somatic symptom condition with significant health-care service burden. While both family and individual factors play an important role in the development and maintenance of PNES, little is known about what predicts urgent health-care use in families with children who have PNES. The aim of the current study was to explore whether child coping and parental bonding styles influence the decision to seek urgent medical care in these families. Methods: Data were analyzed from youth of age 8–18 years, 47 with PNES, and their 25 sibling controls. Parents provided the number of youth emergency room visits and hospitalizations in the preceding year. Youth completed a questionnaire about their coping styles and a measure about their mothers' and fathers' bonding styles. Using a mixed model with family as a random effect, we regressed urgent health-care use on participant type (youth with PNES or sibling), parental bonding style, and youth coping style, controlling for number of child prescription medications. Results: Higher urgent health-care use was associated with having PNES, coping via monitoring, and perceiving one's father to be rejecting and overprotective. Lower urgent health-care use was associated with coping via venting and with perceiving one's mother to be caring and overprotective. Conclusions: This study provides preliminary empirical support for family-based clinical efforts to reduce child urgent health-care use by enhancing effective child coping skills and improving parental response to child impairment and distress in families with youth with PNES.